STUDI KEMAMPUAN MAHASISWA PENDIDIKAN FISIKA DALAM MEMBUAT RENCANA PELAKSANAAN PEMBELAJARAN (RPP) PADA KEGIATAN PRAKTIK PENGALAMAN LAPANGAN II - Gerry Sugiarto; Nely Andriani; Muhamad Yusup (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2020)
Study aims to determine the ability of physics education studentsof FKIP UNSRI to make lesson plans (RPP) physic subjects in class X on the straight motion. The research was conducted on 16 students of physics education in the seventh semester of the academic year 2010/2011 who were PPL II activities. The research method used was descriptive quantitative non – research. Instrument of research form of checklist RPP skill based on Permendiknas number 4 2007 year by referring to APKG 1 and assessment learnig planning from UPPL have been indicator with 3 descriptor. Document of RPP collecting with supporting data interview. The results of the study showed that student s are able to do lesson plans. Of the 10 existing indicators students able to make 6 existing indicators namely competence, basic competence, the formulation of learnings experience determination of learning methods, time, and determination of learning resources. However indicators experienced difficulties namely formulating indicators of achievement of the results of the preparation of subject matter in determining the media for learning tools and determine assessment tools